THE EFFECT OF COUNSELING USING LABOR PREPARATION MODULE ON INCREASING KNOWLEDGE AND ATTITUDE OF PREGNANT MOTHERS - Junengsih Junengsih; Ani Kusumastuti; Juli Oktalia (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2022)
Background: The birth of a baby is the most impressive, enjoyable, and even life-changing life experience for a woman. Every woman wants every birth plan according to her hopes and desires. Birth planning is a simple, clear statement of a woman's preferences for childbirth. The current weakness is that providers often plan births according to their wishes. But less in support as desired by every mother. One alternative in preparing for childbirth is to provide counseling through the provision of modules. The delivery preparation module contains information about a fun delivery guide, it is hoped that every mother can develop a coveted birth plan The purpose of the study was to determine the effect of counseling using the delivery preparation module on the knowledge and attitudes of pregnant women in the third trimester of childbirth. Methods: Quantitative research, quasi-experimental type with pre-test-post-test control group design. The subjects of this study were 3rd trimester pregnant women. Sampling was done by randomized assignment method, the treatment group was in the Pasar Rebo Health Center area and the control group was at the Ciracas District Health Center. Data were analyzed using Wilcoxon test, independent t test and Mann Whitney test. Results: there was a significant difference in the mean score of knowledge (p= 0.0001) and attitude (p= 0.0001) of third trimester pregnant women in post-test-pre-test measurements between the treatment group and the control group. There is a higher difference in scores for the knowledge and attitudes of third trimester mothers who are given intensive counseling using the delivery preparation module in readiness for childbirth Conclusion: the knowledge and attitudes scores of mothers who were given intensive counseling using the delivery preparation module were significantly higher than those who were not given intensive counseling.